Sharia Mental Accounting in The Development of Halal MSMEs for Generation Z in Medan City - Abdul Hadi Ismail; Riyan Pradesyah (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Currently, the government has focused on economic recovery, after the spread of the covid 19 virus that hit the country of Indonesia. One of the instruments taken by the government to improve or restore the economy is by developing MSMEs. In this digital era, the government is developing digital-based MSMEs, so for this reason, the government’s target in this case is MSMEs managed by Generation Z, who understand digitalization. Along with the development of digital-based MSMEs, there are several obstacle factors faced, such as a lack of understanding of financial management, overloading raw material purchases, combining business money with daily money, and the high consumptive level of generation Z. These problems have resulted in many MSMEs that are managed by generation Z. This problem has resulted in many MSMEs managed by generation Z experiencing bankruptcy to bankruptcy, for this reason, sharia mental accounting is needed in building halal MSMEs in generation Z. This study aims to obtain a mental accounting model in building halal MSMEs in Medan City. The research approach used is quantitative, with the SmartPLS analysis tool, with Islamic financial literacy as a mediating variable. The results obtained that mental accounting affects the development of halal MSMEs for Generation Z through financial literacy as a mediating variable. Then Mental accounting from the Maqasid Sharia perspective has a significant effect on the development of halal MSMEs in Medan City through Islamic financial literacy as a mediating variable. Future research is expected to use other mediation variables that can influence Generation Z in developing Halal MSMEs.